Adapting to the test: performing algorithmic adaptivity in Danish schools. Issue 1 (2nd January 2019) - Høvsgaard Maguire, Laura
ABSTRACT: Algorithmic practices are becoming increasingly more central within educational governance. By focusing on the mechanisms of a particular algorithmic testing system in Denmark, this paper highlights how such practices are implicated in the emergence of new accountability infrastructures. It adopts an STS approach drawing specifically upon Michel Callon's concepts framing, overflowing, and re-framing. The paper examines how algorithmic adaptivity has become central in the framing of the Danish national test and traces the ways in which students, teachers, and schools respond to such proceduralized interactions. While algorithmic adaptivity was introduced as a way of providing students with an equal test experience, it also inscribes student adaptability into test practices, generating new student affectivities and teacher responsibilities in the process. The paper argues that this is a matter of adapting to the test and highlights how the mundane practices of testing situations also become a subject of governance.